I am unsure with this one as well. Thanks for helping me!
y = 5^(x + 1) we wnat to get x by itself and then "swap" x and y
In log form we have
log 5 (y) = x + 1 subtract 1 form both sides
log 5 (y) - 1 = x "swap" x and y
log 5 (x) - 1 = y this is the inverse and we can write
g(x) = log 5 (x) - 1 [ this goes in the first blank ]
The graph of the exponential function is a shift of 1 unit to the left
The graph of the log function is a shift 1 unit down from its parent function
for the first 1 theres two options that are very similar, would you need the parenetheses around (x+1) or no?